2012
DOI: 10.1002/ajim.22139
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of a safe resident handling program in nursing homes

Abstract: Decreased costs of worker injury compensation claims and turnover appear at least partially attributable to the SRHP. Future research should examine center-specific factors that enhance program success, and improve measures of turnover costs and healthcare productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
(75 reference statements)
1
24
0
Order By: Relevance
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…Only 5 (50,55,59,76,92) of the 90 studies did not include a measure of lost-time (absenteeism or presenteeism). This is because, in addition to studies with a primary or secondary method that used lost-time (productivity in natural units, HCA, or FCA), several of the ad hoc and output-based methods measured absenteeism or presenteeism.…”
Section: Measuring Time Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…American studies with CBAs also found the interventions (in these cases multifaceted programmes including lifts) to be cost-beneficial 10 12 16 17. Only Lahiri et al 16 reported that in some cases costs exceeded benefits, but in fewer than 50% of the nursing homes participating in the study. Studies noted above adopted an organisational or insurer's perspective in their CBAs.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the effectiveness of the intervention the lower the CER's. Hence, it is imperative to identify factors that can enhance the effectiveness of interventions and possibly make the CERs favourable for implementation 7. Their study examines the role of peer coaching (eg, training) in enhancing the role of an engineering control intervention, namely, overhead lift use, and thereby makes an important contribution to the field.…”
mentioning
confidence: 99%